High‐Efficiency Solution‐Processed Inorganic Metal Halide Perovskite Light‐Emitting Diodes. Issue 31 (13th June 2017) - Cho, Himchan; Wolf, Christoph; Kim, Joo Sung; Yun, Hyung Joong; Bae, Jong Seong; Kim, Hobeom; Heo, Jung‐Min; Ahn, Soyeong; Lee, Tae‐Woo
Abstract : This paper reports highly bright and efficient CsPbBr3 perovskite light‐emitting diodes (PeLEDs) fabricated by simple one‐step spin‐coating of uniform CsPbBr3 polycrystalline layers on a self‐organized buffer hole injection layer and stoichiometry‐controlled CsPbBr3 precursor solutions with an optimized concentration. The PeLEDs have maximum current efficiency of 5.39 cd A −1 and maximum luminance of 13752 cd m −2 . This paper also investigates the origin of current hysteresis, which can be ascribed to migration of Br − anions. Temperature dependence of the electroluminescence (EL) spectrum is measured and the origins of decreased spectrum area, spectral blue‐shift, and linewidth broadening are analyzed systematically with the activation energies, and are related with Br − anion migration, thermal dissociation of excitons, thermal expansion, and electron–phonon interaction. This work provides simple ways to improve the efficiency and brightness of all‐inorganic polycrystalline PeLEDs and improves understanding of temperature‐dependent ion migration and EL properties in inorganic PeLEDs. Abstract : Efficient and bright CsPbBr3 perovskite light‐emitting diodes are achieved using a one‐step fabrication of uniform CsPbBr3 polycrystalline layers on a self‐organized buffer hole injection layer without synthesis of quantum dots. A study of the temperature dependence of current hysteresis and electroluminescence spectrum provides understanding of ion migration, nonradiative pathways, and electron–phonon interaction in the CsPbBr3 perovskite light‐emitting diodes.